Analisis Efektivitas Pembelajaran Kimia Selama Pelaksanaan Pembelajaran Daring di SMA Negeri Se- Kecamatan Sumbawa - Juliantari, Fitri Juliantari; Purwoko, Agus Abhi; Junaidi, Eka (FKIP University of Mataram, 2024)
This study aims to analyze the effectiveness of chemistry learning during the implementation of online learning at State High Schools in Sumbawa district (SMAN 1 Sumbawa, SMAN 2 Sumbawa, and SMAN 3 Sumbawa). This type of research is descriptive with an ex post facto quantitative approach. Sampling technique with the formula of Isaac and Michael with an error rate of 5%, obtained 210 samples. Data collection on the effectiveness of online learning using a closed questionnaire with a Likert scale consisting of 36 statements. Data analysis techniques using descriptive statistical analysis techniques by calculating percentages, results were obtained: indicators of managing the implementation of learning by 72%, communicative processes by 65%, student responses by 52%, learning activities by 68%, and learning outcomes by 70%. The results showed that the effectiveness of chemistry learning during the implementation of online learning with these 5 indicators falls into the effective category with an average of 65%.